Fatwa Ulama dan Diskriminasi Perempuan pada Ranah Pendidikan - Ainurrofiq, Faiq (Fakultas Tarbiyah dan Ilmu Keguruan UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
This article examines the discrimination of women in the education sector perpetuated through the ulama fatwa. The data were taken from the fatwas of Salafi ulama that discussed women's education, both collectively and individually. The structure of the fatwa text is then analyzed using critical discourse analysis at the macro, meso, and microstructural levels. The researcher concludes that Saudi Arabian Salafi scholars use fatwa to practice discriminating against women in education. In this context, the ulama decided (1) differences in the curriculum in girls' schools and boys' schools; (2) instructing women to take specific majors that are deemed appropriate to their nature; (3) prioritizing marriage for women over continuing their studies; (4) enough for women to receive education at the basic education level. The relation between the anti-equality ideology and patriarchal Arab culture influences the construction of ulama fatwas which tend to be discriminatory in women's education. Saudi Arabian Salafi clerics can freely produce and reproduce discriminatory discourse in women's education because Salafi clerics have the power to organize the domain of education in Saudi Arabia, especially before the beginning of the new Saudi Arabia era under the leadership of Muhammad bin Salman.